Deng Xiaoping's Military Modernization and the National Security Interests of the People's Republic of China in the East Asian Region during the Cold War (1980-1991) - Sultani, Zofrano Ibrahimsyah Magribi; Wildani, Ahmad Gussef; Wargi, Faruq Setya; Zidane, Gregorius Alberto Zinadine; Ali, Okada; Rahmawan, Alfin Dwi (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2024)
After Mao Zedong, China arranged military modernization at the 12th National People's Congress on 1-11 September 1982 to become Deng Xiaoping's modernization priority in response to the constellation of political and military forces of the United States of America and the Soviet Union. The research aims to analyze Deng Xiaoping’s military modernization for the interests of China's national security during the Cold War (1980-1991). The research method uses historical methods which consist of problem determination, heuristics, verification, interpretation, and historiography. The results of the research findings are that the modernization of the Chinese military carried out by Deng Xiaoping protected China's national security interests in building and developing its military capabilities in the East Asian region from 1980-1991.